INVITE a virtual reality tour and user education software for the U.P. Diliman Main Library - Carandang. Tristan Joy DR (2005)
The objectives and goals of the study were to create a virtual reality tour software featuring the UPD Main Library and provide a template of this virtual reality tour software for future application in other libraries. The software was named INVITE, which is an acronym for Interactive Virtual Tour Emulation. The name also signifies an invitation to the institution featured by the software. INVITE was developed with the versatility of featuring different types of institutions such as museums, galleries, and other places for learning. The INVITE beta prototypes were tested and evaluated by the University Librarian, the UPD Main Library section heads, several ILIS students and staff and the users of the library for feasible implementation and adaptation of the UPD Main Library.